Preparation of size-tunable sub-200 nm PLGA-based nanoparticles with a wide size range using a microfluidic platform - Yi Bao; Masatoshi Maeki; Akihiko Ishida; Hirofumi Tani; Manabu Tokeshi (PLoS ONE, 2022)
The realization of poly (lactic-co-glycolic acid) nanoparticles (PLGA NPs) from laboratory to clinical applications remains slow, partly because of the lack of precise control of each condition in the preparation process and the rich selectivity of nanoparticles with diverse characteristics. Employing PLGA NPs to establish a large range of size-controlled drug delivery systems and achieve size-selective drug delivery targeting remains a challenge for therapeutic development for different diseases. In this study, we employed a microfluidic device to control the size of PLGA NPs. PLGA, poly (ethylene glycol)-methyl ether block poly (lactic-co-glycolide) (PEG-PLGA), and blend (PLGA + PEG-PLGA) NPs were engineered with defined sizes. Blend NPs exhibit the widest size range (40–114 nm) by simply changing the flow rate conditions without changing the precursor (polymer molecular weight, concentration, and chain segment composition). A model hydrophobic drug, paclitaxel (PTX), was encapsulated in the NPs, and the PTX-loaded NPs maintained a large range of controllable NP sizes. Furthermore, size-controlled NPs were used to investigate the effect of particle size of sub-200 nm NPs on tumor cell growth. The 52 nm NPs showed higher cell growth inhibition than 109 nm NPs. Our method allows the preparation of biodegradable NPs with a large size range without changing polymer precursors as well as the nondemanding fluid conditions. In addition, our model can be applied to elucidate the role of particle sizes of sub-200 nm particles in various biomedical applications, which may help develop suitable drugs for different diseases.